A Real-Business-Cycle model with efficiency wages and a government sector: the case of Bulgaria - Aleksandar Vasilev (Central European Journal of Economic Modelling and Econometrics, 2017)
In this paper we investigate the quantitative importance of e fficiency wages in explaining fluctuations in Bulgarian labor markets. This is done by augmenting an otherwise standard real business cycle model a la Long and Plosser (1983) with unobservable workers e ort by employers and wage contracts as in Shapiro and Stiglitz (1984), as well as a detailed government sector. This imperfection in labor markets introduces a strong propagation mechanism that allows the model to capture the business cycles in Bulgaria better than earlier models. The model performs well vis-a-vis data, especially along the labor market dimension, and in addition dominates the market-clearing labor market framework featured in the standard RBC model, e.g Vasilev (2009).
Keywords: E24; E32; J41; 330; general equilibrium; shirking; efficiency wages; unemployment; Bulgaria